CXCR3, CCR5, and CRTH2 Chemokine Receptor Expression in Lymphocytes Infiltrating Thyroid Nodules with Coincident Hashimoto’s Thyroiditis Obtained by Fine Needle Aspiration Biopsy - Jan Jiskra; Marie Antošová; Jan Krátký; Hana Vítková; Zdeňka Límanová; Helena Marečková; Eliška Potluková (Journal of Immunology Research)
Objective. To determine the expression of chemokine receptors in lymphocytes from thyroid nodules and peripheral blood in patients with and without Hashimoto’s thyroiditis (HT). Patients and Methods. The study included 46 women with thyroid nodules and HT and 60 women with thyroid nodules without HT (controls) who underwent a fine needle aspiration biopsy (FNAB). Expression of chemokine receptors CXCR3, CCR5, and CRTH2 was assessed by flow cytometry in lymphocytes from FNAB samples and from peripheral blood. Results. The percentage of CRTH2+ lymphocytes was higher in nodules with HT in comparison with controls, both in FNAB samples (13.95 versus 6.7%, p=0.008) and in peripheral blood (6.7 versus 5.13%, p=0.047), and positively correlated with serum antibodies to thyroid peroxidase (r=0.243; p=0.026) and negatively correlated with thyroid volume (r=-0.346; p=0.008). Lymphocytes from neoplastic nodules showed a higher expression of both CXCR3 and CCR5 than those from hyperplastic ones. Conclusion. Flow cytometry performed in FNAB samples may serve as a good tool in investigation of intrathyroidal expression of immunological parameters. In our study, the CRTH2 expression on thyroid-infiltrating lymphocytes as well as on lymphocytes from peripheral blood was increased in HT as compared to controls.